2017
DOI: 10.18438/b8fh33
|View full text |Cite
|
Sign up to set email alerts
|

Through the Students’ Lens: Photographic Methods for Research in Library Spaces

Abstract: Objective -As librarians and researchers, we are deeply curious about how our library users navigate and experience our library spaces. Although we have some data about users' experiences and wayfinding strategies at our libraries, including anecdotal evidence, statistics, surveys, and focus group discussions, we lacked more in-depth information that reflected students' real-time experiences as they move through our library spaces. Our objective is to address that gap by using photographic methods for studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…After an extensive coding process, a thematic analysis uncovered a number of findings relating to library services, space, and student research habits. Future research could pursue a number of different directions, including focusing upon or incorporating additional ethnographic methods, such as participant-driven photo elicitation methods (Bedi & Webb, 2017) …”
Section: Resultsmentioning
confidence: 99%
“…After an extensive coding process, a thematic analysis uncovered a number of findings relating to library services, space, and student research habits. Future research could pursue a number of different directions, including focusing upon or incorporating additional ethnographic methods, such as participant-driven photo elicitation methods (Bedi & Webb, 2017) …”
Section: Resultsmentioning
confidence: 99%
“…In our own research, we found that photographs can help facilitate in-depth discussions in other ways. In particular, we heard from several participants who described the process of making photographs as a way to overcome intimidating language barriers that would otherwise deter them from participating in the research (Bedi & Webb, 2017). This finding leads us to hypothesize that photoelicitation may be a tool that can help encourage broader participation from international students on our campuses, leading to the inclusion of more diverse opinions and experiences in library research (Bedi & Webb, 2017).…”
Section: Photo-elicitation Can Facilitate the Interview Processmentioning
confidence: 98%
“…In our own research, we use PDPE methods to investigate users' library wayfinding strategies and shed light on students' experiences in library spaces (Bedi & Webb, 2017). The insights we gained have already begun to inform renovation plans and signage improvements to our physical spaces.…”
Section: Photo-elicitation For Studying Users Experience In Library Smentioning
confidence: 99%
See 2 more Smart Citations